Analysis on the Characteristics of Water Pollution Caused by Underground Mining and Research Progress of Treatment Technology - Xinfeng Wang; Yuhao Gao; Xiaojun Jiang; Qiao Zhang; Wengang Liu (Advances in Civil Engineering)
Coal is the primary source of energy in China’s energy structure system. With the large-scale mining of mineral resources, a large amount of mine water will be produced in the process of development, construction, and production, which will pollute and damage the ecological environment of mine water. At present, China vigorously advocates coal revolution, implements low-carbon economy, and carries out clean production of energy development and utilization. Green mining, precision mining, and other strategic ideas have been applied to mine development to guide production practice. This paper does an in-depth analysis of the physical, chemical, biological, and environmental characteristics of mine water, puts forward the basic classification of mine water, and points out the characteristics of environmental hazards of mine water. Aiming at different types of mine water, such as mine wastewater, drainage water, goaf water, mine water with suspended solids, high salinity mine water, acid mine water, and mine water with special pollution, the paper puts forward the mine water treatment and resource utilization technology with different characteristics and strong pertinence. On this basis, the comprehensive treatment and development direction of mine water in the future are prospected.